If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -4 = 2(2x + 6) Reorder the terms: -4 + 3x = 2(2x + 6) Reorder the terms: -4 + 3x = 2(6 + 2x) -4 + 3x = (6 * 2 + 2x * 2) -4 + 3x = (12 + 4x) Solving -4 + 3x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -4 + 3x + -4x = 12 + 4x + -4x Combine like terms: 3x + -4x = -1x -4 + -1x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 -4 + -1x = 12 + 0 -4 + -1x = 12 Add '4' to each side of the equation. -4 + 4 + -1x = 12 + 4 Combine like terms: -4 + 4 = 0 0 + -1x = 12 + 4 -1x = 12 + 4 Combine like terms: 12 + 4 = 16 -1x = 16 Divide each side by '-1'. x = -16 Simplifying x = -16
| 2c-5=15 | | 44+20=h | | P+p+o=4 | | 12-s=14 | | 98=-3(-2x-7)+5x | | 25g-5g^2=0 | | -4x+8=-2x+2 | | x+3x=2000 | | 5x(5x-4)= | | -4a+4(3a+3)=-8-2a | | 2y=6(-2)-10 | | p+1.6-0.4=-12 | | 2x+5y+2z=10.50 | | -5x^4+20x^2=0 | | 4x=-3x-7 | | 7y+6=180 | | 15=1.25h | | 8+8x+2x=2x+16 | | f(x-1)=x^2-14x+54 | | (2x+3.75)x-0.5=11.5 | | 3*8+2*-2= | | 6(3n-5)=(7n+6)+3 | | 9m^2+2m=10 | | 12+b=10 | | -54=a-49 | | 72=-6m | | Log(t-3)=(17-4t) | | (3x-18)(8x+32)=0 | | .5x^4-.5=0 | | -6p=58 | | -36g+40g+19g+-47g+18g=42 | | 3(8)+2(-2)= |